2017
DOI: 10.1186/s13568-017-0360-y
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of active compound, genipin, from Gardeniae Fructus using immobilized glycosyl hydrolase family 3 β-glucosidase from Lactobacillus antri

Abstract: Geniposide is an iridoid glycoside, which is abundant in Gardeniae Fructus. Despite the various pharmaceutical effects of geniposide on a human body, its hydrolysis into a smaller molecule, genipin, by β-glucosidase produced by bacteria in the intestines is particularly important to improve geniposide uptake into the body. Since geniposide is much more abundant in Gardeniae Fructus than its aglycone genipin, we herein transformed geniposide into genipin using purified recombinant β-glucosidase from Lactobacill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 31 publications
(34 reference statements)
1
16
0
Order By: Relevance
“…Although the utilization of the disaccharides by L. plantarum and L. pentosus in FCJM at pH 3.7 ± 0.1 could occur during a prolonged incubation, β‐glucosidases are inhibited at pH below 4.0 (Kim, Lee, & Ma, 2017; Takase & Horikoshi, 1988; Yeoman et al, 2010; Zhong et al., 2016). While β‐glucosidases occur in many organisms, the activity of the enzymes derived from thermophilic bacteria and lactobacilli is known to be severely compromised at a pH of 4.0 with a 20% enzyme stability, as compared to a 40% stability at pH 5.0 (Kim et al., 2017; Takase & Horikoshi, 1988; Yeoman et al, 2010; Zhong et al., 2016). Growth of L. plantarum is known to stop at a pH of 3.3 with the cessation of acid production at a pH of 3.0 (McDonald, Fleming, & Hassan, 1990).…”
Section: Resultsmentioning
confidence: 99%
“…Although the utilization of the disaccharides by L. plantarum and L. pentosus in FCJM at pH 3.7 ± 0.1 could occur during a prolonged incubation, β‐glucosidases are inhibited at pH below 4.0 (Kim, Lee, & Ma, 2017; Takase & Horikoshi, 1988; Yeoman et al, 2010; Zhong et al., 2016). While β‐glucosidases occur in many organisms, the activity of the enzymes derived from thermophilic bacteria and lactobacilli is known to be severely compromised at a pH of 4.0 with a 20% enzyme stability, as compared to a 40% stability at pH 5.0 (Kim et al., 2017; Takase & Horikoshi, 1988; Yeoman et al, 2010; Zhong et al., 2016). Growth of L. plantarum is known to stop at a pH of 3.3 with the cessation of acid production at a pH of 3.0 (McDonald, Fleming, & Hassan, 1990).…”
Section: Resultsmentioning
confidence: 99%
“…The hydrolysis of geniposide to genipin by β-glucosidase could also be studied directly by using purified enzymes. Hence, the immobilized glycosyl hydrolase family 3 β-glucosidase has been effectively used to convert geniposide in a hot-water extract of G. fructus into genipin [ 31 ]. With respect to probiotic applications, the role of lactic acid bacteria ( Lactobacillus sp.)…”
Section: Physicochemical Properties and Associated Pharmacokineticmentioning
confidence: 99%
“…The mechanism for the microbial transformation of gardenoside is to ferment gardenoside using a b-glucosidase-producing bacterium, and b-glucosidase can break the chemical bond of gardenoside to produce genipin. 12 Qian et al 13 demonstrated that the Lactobacillus casei strain Shirota can enhance the anti-proliferative effect of gardenoside on human oral squamous cell carcinoma HSC-3 cells using in vitro cell experiments. Kim et al 14 used the b-glucosidase produced by Lactobacillus antri (rBGLa) to hydrolyze gardenoside to a smaller molecule of genipin and expressed it in E. coli to increase the content of genipin.…”
Section: Introductionmentioning
confidence: 99%
“…12 Qian et al 13 demonstrated that the Lactobacillus casei strain Shirota can enhance the anti-proliferative effect of gardenoside on human oral squamous cell carcinoma HSC-3 cells using in vitro cell experiments. Kim et al 14 used the b-glucosidase produced by Lactobacillus antri (rBGLa) to hydrolyze gardenoside to a smaller molecule of genipin and expressed it in E. coli to increase the content of genipin. Genipin has signicant effects on the digestive system, cardiovascular system, and central nervous system diseases, and also has certain anti-inammatory, antihypertensive, and laxative effects, and can be used to treat so tissue damage and liver diseases.…”
Section: Introductionmentioning
confidence: 99%